Analysis and Design Web Based System in LPPM UMN - Daniel Subandi; Friska Natalia (ULTIMA InfoSys, 2015)
Institute for Research and Community Service, or called LPPM is a forum for researchers to conduct studies with internal and national scales. LPPM UMN is one of the institutions that provide the container for UMN researchers. However, in the LPPM UMN itself still does not have a webbased system that can be accessed anywhere. This website will be able to share knowledge amongst lecturers by downloading study results that have been done before. After collecting all the requirements, an application is designed using the Rapid Application Development for a limited time spent. The application is built by designing a website and applying MySQL database and PHP programming language with CodeIgniter framework 2.2.2. This website is divided into 3 parts; admins, reviewers, and researcher. Admins are able to see the whole proposal which is sent and appoint a reviewer for one of the proposals. Reviewers have some facilities to review research proposals that have been uploaded. Researchers are able to upload a research proposal. Index Terms - LPPM, Knowledge Management, Research, Website.